2020
DOI: 10.1007/s41403-020-00102-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of National Aerosol Facility (NAF) in Designing of a Ventilation System for Isolation Rooms to Minimize Interpersonal Exposure of Sneezing/Coughing

Abstract: With the outbreak of pandemic COVID-19, protection of public and health workers has become a national priority. In this regard, it is desirable to study the coughing-and sneezing-generated pathogen aerosols, its dispersion and transportation in isolation rooms, clinics, confined spaces and other general public places to evolve efficient ventilation system along with suitable protective measures to limit the spread of the virus. The present paper describes the overall experimental scheme supported with computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Novoselac and Srebric ( 2003 ) reported that the choice of ventilation strategy defined the correlations between the removal of contaminant and air-exchange efficiency. Singh and Tripathi ( 2020 ) propose experimental and computational fluid dynamics models to establish an understanding for improved ventilation design for hospitals, isolation rooms and enclosed spaces. Better ventilation when combined with efficient filtering of air will help sanitize and improve the quality of air in living rooms and isolation rooms.…”
Section: Space Sanitizationmentioning
confidence: 99%
“…Novoselac and Srebric ( 2003 ) reported that the choice of ventilation strategy defined the correlations between the removal of contaminant and air-exchange efficiency. Singh and Tripathi ( 2020 ) propose experimental and computational fluid dynamics models to establish an understanding for improved ventilation design for hospitals, isolation rooms and enclosed spaces. Better ventilation when combined with efficient filtering of air will help sanitize and improve the quality of air in living rooms and isolation rooms.…”
Section: Space Sanitizationmentioning
confidence: 99%
“…These simulations claimed to have potential in devising accurate guidelines for separation distances between neighbors within a group, design better masks, and minimize the spread of the disease. Singh and Tripathi ( 2020 ) proposed to study ventilation design of a room for effective transportation of coughing- and sneezing-generated pathogen aerosols. Joshi ( 2020 ) developed an innovative chamber christened as COVid SAmple Collection Kiosk (COVSACK) to protect the healthcare provider from getting infected while collecting samples.…”
Section: Development Of Computer Models and Apps For Managing The Panmentioning
confidence: 99%
“…The effects of relative humidity and wind velocity on the evaporation and dispersion of the droplets in an open space were evaluated by Li et al [16]. By numerical simulation of sneezing in a room, Singh and Tripathi developed a model for droplets transmission [17]. Experiments of Chaudhuri et al [18] showed that the droplets evaporation time depends on the ambient temperature.…”
Section: Introductionmentioning
confidence: 99%